Menjadi Good Citizen Melalui Pendidikan Kewarganegaraan di Era Globalisasi - Auliah Safitri; Suharno Suharno (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2019)
The purpose of this article is to examine Thomas Lickona's theories about how to be a good citizen or a good character of citizens. This article was compiled using the library research method, namely the method of data collection carried out by utilizing library resources and materials. The results obtained that a person can be said to be a good citizen if he is able to carry out his duties and obligations properly in living life as a citizen. To create a good character of citizens and answer challenges and opportunities for global life, a new paradigm of education is needed. Global Civic Education is the fastest form of education reform in the current era. Global Citizenship Education is considered as one of the subjects that can prepare global citizens to be able to understand various global problems. Global citizenship education basically has a very good goal to create an equal perception of the duties, rights and obligations of citizens in carrying out the duties of being good citizens and not to distinguish between equality of race, ethnicity, culture, religion or groups that are equally have human rights.